2012
DOI: 10.1186/1477-7819-10-84
|View full text |Cite
|
Sign up to set email alerts
|

Nonerosive gastroesophageal reflux disease and mild degree of esophagitis: Comparison of symptoms endoscopic, manometric and pH-metric patterns

Abstract: BackgroundOur aim in the present study was to compare patients presenting with gastroesophageal reflux disease in the presence or absence of mild-grade esophagitis (grade I or II according to the Savary-Miller classification).MethodsBetween 2005 and 2007, 215 patients with gastroesophageal reflux disease (67 with reflux associated with grade I or II esophagitis and 148 without esophagitis) were evaluated at the Department of Surgery, University Hospital Tor Vergata, Rome, and were included in the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
3
4
1
Order By: Relevance
“…In our study, we found an unusual prevalence of hiatal hernia in contrast with some authors [ 23 , 24 ]. We are not able to explain this data, however one theory is that it may be due to the excessive attention with which this condition was searched for.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, we found an unusual prevalence of hiatal hernia in contrast with some authors [ 23 , 24 ]. We are not able to explain this data, however one theory is that it may be due to the excessive attention with which this condition was searched for.…”
Section: Discussioncontrasting
confidence: 99%
“…The incidence of patients with hiatal hernia and no H. pylori infection was higher than patients with H. pylori infection and hiatal hernia (91 versus 31; P <0.0001). Moreover, according to a past study [ 23 ] and this present one, the incidence of hiatal hernia did not associate with RE ( P <0.0001). We found significant correlation between H. pylori infection and hiatal hernia, considered by some authors as a supporting element of GERD, and significantly associated with the development of esophagitis [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 62%
“…When patients with endoscopically proven reflux esophagitis were compared with normal volunteers of similar age, the patients had a higher prevalence of hiatal hernia, larger His angle, shorter LES and abdominal esophageal length, wider opening of the MI‐LES during the relaxation phase, and a thicker distal esophageal wall, especially those with high‐grade reflux esophagitis. These differences have been described in previous investigations . Therefore, our findings confirmed the accuracy of dynamic image analysis using area detector CT for detecting morphological changes of the EGJ in patients with reflux esophagitis.…”
Section: Discussionsupporting
confidence: 91%
“…These differences have been described in previous investigations. 14,[23][24][25][26][27][28] Therefore, our findings confirmed the accuracy of dynamic image analysis using area detector CT for detecting morphological changes of the EGJ in patients with reflux esophagitis. The presence of hernia in reflux esophagitis patients seems to be fewer than that examined by endoscopy and esophagogram.…”
Section: Figuresupporting
confidence: 81%
“…Most of the patients with classical reflux signs do not reveal endoscopic signs of oesophagitis. This group of patients is considered as a mild form of gastrooesophageal reflux disease (13). A commonly shared idea by many investigators is that the incidence of symptoms does not differ according to the presence or absence of oesophagitis in gastro-oesophageal reflux disease patients (15,16).…”
Section: H Pylori (+)mentioning
confidence: 99%